MENANAMKAN SIKAP DALAM TOLERANSI BERAGAMA PADA SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN IPS (MULTICULTURAL BASED) - Nabila Cahyaningtiyas; Desi Nur Rahayu (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
ABSTRACT Religious differences that often occur among elementary school children trigger conflicts between majority and minority religious groups. The emergence of these conflicts shows the low attitude of religious tolerance in elementary school students. This research aims to instill an attitude of religious tolerance through multicultural-based social studies learning, where multiculturalism teaches students to always appreciate differences. This article uses a type of literature study method or literature review on the cultivation of tolerance in elementary school students through learning social studies (ips). The steps in the literature study are (1) choosing a topic; (2) determining the focus of information; (3) formulating the focus of research; (4) collecting data sources; (5) preparing data presentation (6) compiling a report. The method/technique of data collection in this article uses the documentation method, meaning that researchers look for data relevant to the topic by using reading materials such as books, articles and journals. The results showed that multicultural-based social studies learning has a great influence on the cultivation of religious tolerance attitudes in elementary school students.